A Systematic Review of the Literature on Foreign Brides’ Adaptation Experiences in Korea - HEH YOUN SHIN; Esther Prins (Adult Education Research Conference, 2017)
The purpose of this qualitative systematic review is to synthesize the literature on foreign brides in Korea to examine how they are represented and how sociocultural contexts shape their experiences and adjustment.
Keywords: foreign brides; Korea; systematic literature review